Promotion of myotube differentiation and attenuation of muscle atrophy in murine C2C12 myoblast cells treated with teaghrelin. (5th January 2020) - Hsieh, Sheng-Kuo; Lin, Hsin-Yi; Chen, Chun-Jung; Jhuo, Cian-Fen; Liao, Keng-Ying; Chen, Wen-Ying; Tzen, Jason T.C.
Abstract: This study aimed to investigate the effects of teaghrelin, an active ingredient of Chin-shin oolong tea, on murine C2C12 myoblast cells. Under high serum conditions, teaghrelin inhibited C2C12 cell proliferation, indicating a cell cycle arrest and cessation of proliferative progression. Teaghrelin promoted pro-differentiation of C2C12 cells as evidenced by a progressively elongated morphology, as well as the induction of muscle specific myogenin, myosin heavy chain (MHC), and MyoD. The formation of multinucleated myotubes, and the increase of MHC-positive immunoreactivity within the myotubes, further reflected a complete differentiation and maturation of the contractile skeletal muscle cells induced by teaghrelin. Like ghrelin, teaghrelin attenuated dexamethasone-decreased myotube diameter, indicating its protective effects against skeletal muscle atrophy. Additionally, the expressions of Atrogin-1 and MuRF-1 ubiquitin E3 ligase were reduced. In conclusion, the results highlight a possibility of developing teaghrelin as a functional food for the prevention or therapeutic treatment of disease-associated skeletal muscle atrophy. Graphical abstract: Image 1 Highlights: Teaghrelin attenuated C2C12 myoblast cell proliferation. Teaghrelin promoted C2C12 cell differentiation and myotube formation. Teaghrelin attenuated dexamethasone-induced myotube atrophy. Teaghrelin attenuated dexamethasone-induced ubiquitin E3 ligase expression.